A genomic region involved in the formation of adhesin fibers in Bacillus cereus biofilms - Caro-Astorga, Joaquín; Pérez-García, Alejandro; de Vicente, Antonio; Romero, Diego (Frontiers in Microbiology, 2015)
Bacillus cereus is a bacterial pathogen that is responsible for many recurrent disease outbreaks due to food contamination. Spores and biofilms are considered the most important reservoirs of B. cereus in contaminated fresh vegetables and fruits. Biofilms are bacterial communities that are difficult to eradicate from biotic and abiotic surfaces because of their stable and extremely strong extracellular matrix. These extracellular matrixes contain exopolysaccharides, proteins, extracellular DNA, and other minor components. Although B. cereus can form biofilms, the bacterial features governing assembly of the protective extracellular matrix are not known. Using the well-studied bacterium B. subtilis as a model, we identified two genomic loci in B. cereus, which encodes two orthologs of the amyloid-like protein TasA of B. subtilis and a SipW signal peptidase. Deletion of this genomic region in B. cereus inhibited biofilm assembly; notably, mutation of the putative signal peptidase SipW caused the same phenotype. However, mutations in tasA or calY did not completely prevent biofilm formation; strains that were mutated for either of these genes formed phenotypically different surface attached biofilms. Electron microscopy studies revealed that TasA polymerizes to form long and abundant fibers on cell surfaces, whereas CalY does not aggregate similarly. Heterologous expression of this amyloid-like cassette in a B. subtilis strain lacking the factors required for the assembly of TasA amyloid-like fibers revealed i) the involvement of this B. cereus genomic region in formation of the air-liquid interphase pellicles and ii) the intrinsic ability of TasA to form fibers similar to the amyloid-like fibers produced by its B. subtilis ortholog.